KUFRA DEPRESSION A STUDY IN ECONOMIC DEVELOPMENT - Hassan , Dr. Mohamed Ibrahim (مجلة كلية الاداب, 1972)
Precise recommendations and conclusions recorded here are based primarily on a fieldtrip study of the Department of Geography, Univer sity of Libya, during the period 19-24 March, 1970. Agriculture in the Depression forms the principal source of wealth for the majority of the population. The utmost importance of agriculture and its economic and social aspects strengthen the fact that to develop agriculture means to improve the standard of living of the great majority of the population. The soils of the depression are dominated by three factors of climatic regime, geomorphology, and parent material: (A) The very high rate of surface evaporation due to the arid nature of climate, leads to a capillary gradient from the subsoil to the surface. (B) The surface of the depression ground rises and falls to give an un even relief. In these small basins, ground water collect by lateral seepage. Șuch water evaporates intensely from these seepage areas with result that salt accumulates at the soil surface and within the upper part of the 199 soil profiles, creating aSebkhats) or salted soils in the lowest parts. These saline soils contrast with the non-saline soils which form the majority of the land of the oases. (C) Parent rocks of the whole depression are sandstones of lower crc taceous age. These are predominantly continental sandstones, with some conglomerates, siltstones, quartzite, and silicified wood. This formation weathers to give soils of sandy texture. The soils of the Kufra area are broadly of two main types : (A) Small patches of Sebkhats or saline soils which require drainage works and further study for fertilisation and crop suitability. (B) The majority of the Kufra soils are coarse textured desert soils which show no accumulation of salts in their profiles. This fact is very important for the behaviour of the soils through irrigation. Due to low content of organic matter in the soils and the low con tents of fine material like silt and clay, the structure of the soils is very weakly developed. The most efficient way to increase soil fertility and crop yields is to apply animal manures or green legume as berseem whose root can be ploughed into the soil. Agriculture in these oases is in great need of a well-planned programme of fertilizer application to the soil which is poor in potassium, phosphate and nitrogen. The agriculture of the area is based on irrigation from machine or animal pumps. It is envisaged that this method of agriculture will in crease in intensity in the future as more and more farmers install machine pumps. From the point of view of water supply, the Kufra area is well supplied for future developments. Fresh water is drawn from an aquifer within the Nubian Sandstone to depths up to 200 metres. Assuming that the present rates of water-extraction are increased even tenfold, the life of the aquifer should exceed 500 years. To undertake organized measures for increasing the production of animal husbandry, primarily with the aim of meeting the local needs, the following steps should be taken: 200